Empire and national character: British imperialism in books from the "Third Reich" - Stiles, Victoria (2015)
This thesis examines the variety of representations and rhetorical deployments of the theme of British Imperialism within books published in the “Third Reich”. The thesis considers these books not only as vehicles for particular ideas and arguments but also as consumer objects and therefore as the product of a series of compromises between the needs of a host of actors, both official and commercial. It further traces the origins of the component parts of these texts via the history of reuse of images and extracts and by identifying earlier examples of particular tropes of “Englishness” and the British Empire.